MTHFR C677T is not associated with autism spectrum disorder in a Mexican cohort - Morales-Marín, Mirna Edith; Náfate-López, Omar; Gómez-Cotero, Amalia Guadalupe; Cid-Soto, Miguel Angel; Nicolini, Humberto; Castro-Martínez, Xochitl Helga (Frontiers in Psychiatry, 2025)
Using genetic approaches to study autism spectrum disorder (ASD) is essential to understanding the etiology of the condition. The C677T variant has emerged as a risk factor, and here we present the first association study of this variant in a Mexican population with ASD. Our objective was to assess the variant MTHFR C677T (rs1801133) in a group of Mexican patients with ASD through a case-control association analysis. We found no significant association of MTHFR C677T and ASD, with no rate differences between cases and controls (C vs T: odds ratio = 0.9698, 95% confidence interval = 0.7773–1.21, P = 0.7858). Results of this and other studies evaluating the link between ASD and this variant have been controversial. Our findings suggest that other ancestry-related factors may play a role.